Epidemiology and patterns of the hand and distal forearm fractures at King Abdul-Aziz Medical City, Riyadh, KSA. Issue 1 (February 2016) - AlMugren, Turki S.; Al-Namlah, Abdullah; Alkubaidan, Fahad; AlOtaibi, Humoud; AlZimami, Ibrahim
Abstract: Objectives: The hand is the most commonly fractured site in the body, as it represents 17–25% of all body fractures. The metacarpal bone of the small finger is the most commonly fractured hand bone. This study aimed to determine the epidemiology and frequency of various fractures of the hand and the distal forearm in adults with a view to identifying patients who required surgical treatment. Methods: This retrospective review examined the medical records of all hand and distal forearm X-rays performed on adult patients who presented to the emergency room of King Abdul-Aziz Medical City from January 2010 to December 2011. Results: In this study, we reviewed 2993 X-rays of the hand and the distal forearm. One-third of these X-rays confirmed fractures (n = 948), and more than two-thirds of these fractures were recorded in male patients (n = 702). There was no major difference in the distribution of fractures between the left and right hand. Half of these fractures (n = 472) were found in the young age group (18–30 years). The study showed that the phalanges had the highest proportion of fractures (n = 362, 40%). Distal forearm fractures represented one-third of all registered fractures (n = 287). Almost half of the metacarpal fractures were found in the 5th metacarpal (n = 104), confirming that the 5th metacarpal bone is the most commonly fractured bone in the hand. One-fifth of all fractures were surgically managed (n = 190, 20%). Conclusion: One-third of the reviewed X-rays identified hand and distal forearm fractures. Both hands were affected equally. Patients in the young age group are more prone to have fractures, and phalanges had the highest proportion of fractures followed by the distal forearm.